Studi Pengujian SEM (Scanning Electron Microscopy) Komposit Bermatrik Ebonit Dengan Kandungan Sulfur 40 Phr Yang Diperkuat Serat Rami Dan Bambu Dengan Kandungan Masing-Masing 30 Phr - Najakh, Muhammad Abdun; , Dr. Joko Sedyono (2017)
Plastic is a common material that is often used to manufacture the product in an industry, especially the automotive industry. However, plastic has the disadvantage that the difficulty of the decomposition of waste that take a long time. It needs a better substitute material of plastic that is composite. Composite is a better solution because the constituent materials used can use natural materials, ranging from fibers and matrix. This is what makes the composite an environmentally friendly material that is biodegradable and does not cause the problems of waste. And the method of testing done on this composite is SEM (Scanning Electron Microscopy), in which the purpose of the test is to look at the microstructure of the composite. From the observation of micro structure capable of showing bonding characteristics of the constituent fibers that reinforce composites. For composites used in this study using ebonite matrix with fiber in the form of Rami and Bamboo. SEM test results show that the fiber bonding glue with ebonite Rami more than the bond of Bamboo fiber is seen to be apart of ebonite. Keywords : Composite, Natural Fibers, SEM